No Increased Risk of Fracture in Patients Receiving Antimuscarinics for Overactive Bladder Syndrome: A Retrospective Cohort Study. (9th January 2018) - Kao, Li‐Ting; Huang, Chao‐Yuan; Lin, Herng‐Ching; Chu, Chi‐Ming
Abstract: To date, the actual relationship between antimuscarinics for overactive bladder (OAB) syndrome and the subsequent risk of a fracture remains unclear. The aim of this retrospective cohort study was to demonstrate the association between antimuscarinics for OAB and fractures using a large population‐based data set. Data used in this study were taken from the Taiwan Longitudinal Health Insurance Database 2005. We identified 2927 OAB patients who received antimuscarinics as the study cohort and 11 708 matched OAB patients who did not receive antimuscarinics as the comparison cohort. Each individual was tracked for a 3‐year period to define those who received a diagnosis of a fracture. Stratified Cox proportional hazard regression analyses were conducted to estimate the association between antimuscarinics for OAB and a subsequent fracture. Results revealed that the incidence rate of fracture per 100 person‐years within the 3‐year follow‐up period were 3.01 (95% confidence interval [CI], 2.65–3.40) for OAB patients who received antimuscarinics and 2.77 (95%CI, 2.60–2.95) for those OAB patients who did not receive antimuscarinics. The adjusted hazard ratio (HR) for a subsequent fracture for OAB patients who received antimuscarinics was 1.11 (95%CI, 0.97–1.28) compared with those OAB patients who did not receive antimuscarinics. Consequently, we concluded that antimuscarinics for OAB was not significantly predictive of fracture.